2016
DOI: 10.5761/atcs.oa.15-00306
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a Reticulated Trabecula-Like Structure Increases the Risk for the Recurrence of Primary Spontaneous Pneumothorax after Thoracoscopic Bullectomy

Abstract: Introduction: Deteriorated alveolar structure at the base of blebs and bullae is known as the reticulated trabecula-like structure. Its clinical significance in primary spontaneous pneumothorax (PSP) remains unclear. This study aimed to investigate the impact of the structure on recurrence of PSP after video-assisted thoracoscopic surgery (VATS) bullectomy. Methods: Between April 2010 and March 2014, 80 cases of PSP in 76 patients who underwent VATS bullectomy using endoscopic staplers were included. The stapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…15 Investigators have identified specific ultrastructural abnormalities in the elastin fibers found in the apical regions of the lungs of individuals undergoing blebectomy/bullectomy, supporting the concept that localized connective tissue abnormalities lead to blebs and bullae development. 16 Spontaneous rupture of blebs or bullae is commonly believed to be the primary mechanism leading to pneumothorax. However, several observations challenge this idea.…”
Section: Pathophysiologymentioning
confidence: 99%
“…15 Investigators have identified specific ultrastructural abnormalities in the elastin fibers found in the apical regions of the lungs of individuals undergoing blebectomy/bullectomy, supporting the concept that localized connective tissue abnormalities lead to blebs and bullae development. 16 Spontaneous rupture of blebs or bullae is commonly believed to be the primary mechanism leading to pneumothorax. However, several observations challenge this idea.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The mechanism of PSP has generally been suggested to be associated with the rupture of a subpleural bleb or bullae [ 12 , 13 ]. Although not sufficient, a few studies suggested the neo-bullae genesis theory to explain PoR of PSP [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of PSP has generally been suggested to be associated with the rupture of a subpleural bleb or bullae [ 12 , 13 ]. Although not sufficient, a few studies suggested the neo-bullae genesis theory to explain PoR of PSP [ 10 , 12 ]. Onuki et al evaluated nine PoR cases (mean follow-up duration, 869 ± 542 days) with CT, and seven of them had different types of neo-genetic bullae, which were found within 3 cm of the staple lines [ 10 ].…”
Section: Discussionmentioning
confidence: 99%